Numeric Factors Affecting the Premium Mobile Numbers’ Auction Result: Thailand Case Study - boonmee, poramate (Journal of Digital Communications, 2022)
This article aimed to study the numeric factors influencing the premium mobile numbers’ auction result, and to develop a model by using the Logit model. This study was an experimental research from the auction data of office of the NBTC (Auction No. 2/2562). The study found that the format of premium numbers and auspicious numbers (excluding the auspicious sum variable) could significantly influence the auction probability. The results pointed out that premium numbers with 4 identical consecutive numbers and symmetrical numbers (mirror) were likely to have the highest chance of being auctioned - at 19.03% and 14.20% respectively. In addition, the author also determined the optimal cut-off point for measuring the correctness of derived model based on Youden’s index. The result showed that the optimal cut-point was at 0.60 with the accuracy rate of prediction as high as 82.39%. This study could enhance Office of the NBTC’s efficiency in auction managing and administering by setting an auction order in accordance with the trend of the result. Additional criteria on auspicious numbers should also be issued to reflect the intention of the premium number allocation.